Shear strength properties of structural lightweight reinforced concrete beams and two-way slabs using palm kernel shell course aggregates - Acheampong, Alex (2016)
A thesis submitted to the Department of Building Technology, College of Art and Built Environment in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Building Technology, 2015